Bahasa dalam Pembelajaran Musik: Metode Kodály sebagai Alat untuk Berkomunikasi dalam Ansambel - Riyan Hidayatullah (Aksara: Jurnal Bahasa dan Sastra, 2019)
In music learning, the term ‘notation’ is used to refer to the means of communication, which consists of  grand staff and numbered notations. However, the method that is widely used by music teachers in music ensemble classes is the Kodály Method. This study was aimed at investigating students’ ability to perform Kodály hand sign technique, which was conducted in Dance Education Study Program, Lampung University. It adopted a descriptive-qualitative approach. The data were taken from a lecture sub-topic of “melody”, which was  then compared to the sub-topic of “rhythmic”. The results showed that students understood and received the Kodály technique material more quickly. In conclusion, the students found it much easier to perform the Kodály hand sign technique than the grand staff notation in ensembles because the technique emphasized on hand rote which was then applied to a pianika or recorder. Keywords: Kodály method, music language, ensemblesDOI: http://dx.doi.org/10.23960/aksara/v20i1.pp25-34